2011
DOI: 10.1097/igc.0b013e3181ffccc1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients Undergoing Radical Hysterectomy for Cervical Cancer of High-Risk Histological Subtypes

Abstract: Structured Abstract Introduction The most common types of cervical cancer are squamous cell carcinoma, adenocarcinoma, and adenosquamous carcinoma, referred to here collectively as SA cervical cancer. Other types of cervical cancer, referred to here collectively as nonsquamous/nonadenocarcinoma (NSNA) cervical cancer, include neuroendocrine, small cell, clear cell, sarcomatoid, and serous tumors. Anecdotally, NSNA tumors seem to have a worse prognosis than their SA counterparts. We sought to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The histologic subtype of this patient was small cell carcinoma. In fact, high-risk histologies, such as neuroendocrine and serous tumors of the cervix, have poor prognosis than squamous cell carcinoma and adenocarcinoma [17]. Meanwhile, Lee et al [18] reported that there was no significant difference in survival outcomes between adenocarcinoma and adenosquamous carcinoma in early-stage cervical cancer patient after radical hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The histologic subtype of this patient was small cell carcinoma. In fact, high-risk histologies, such as neuroendocrine and serous tumors of the cervix, have poor prognosis than squamous cell carcinoma and adenocarcinoma [17]. Meanwhile, Lee et al [18] reported that there was no significant difference in survival outcomes between adenocarcinoma and adenosquamous carcinoma in early-stage cervical cancer patient after radical hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rare histologies-e.g. neuroendocrine carcinoma and glassy cell carcinoma-were not excluded, despite potentially having different biological behaviors from those of squamous cell carcinoma (SCC), adenocarcinoma, or adenosquamous carcinoma [15,16]. Finally, most of the studies were limited to small samples and single institutions.…”
Section: Introductionmentioning
confidence: 98%
“…According to ESMO, tumour risk assessment includes nodal status, lymphovascular space invasion, tumour size and histological type. Among the factors mentioned in the literature that have shown prognostic value in cervical cancer are also tumour differentiation, Ki67, expression of p53 and serum Ca 125 level [2, 12, 25-27]. Poor prognosis is associated with tumour invasion >10 mm, tumour size >2 cm, age <65 years, FIGO stage >I, elevated serum level of Ca 125 and the presence of lymph node metastases [9, 28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, this group of patients belongs to the nonsquamous/non-adenocarcinoma category, along with neuroendocrine, small cell, clear cell and sarcomatoid tumours, present in less than 5% of all malignancies of the uterine cervix [2]. According to the data in the literature, although the incidence of cervical cancer has declined over time, the incidence of nonsquamous/non-adenocarcinoma and adenocarcinoma histologic subtypes has increased, especially in young women [2, 3]. USCC is a sporadic pathological form accounting for only less than 1% of all cervical cancer cases [4-7].…”
Section: Introductionmentioning
confidence: 99%